ANALYSIS OF MATERNAL REFERRAL SYSTEM IN INDONESIA WITH FISHBONE DIAGRAM - Rahmah Yani; Sabarinah Prasetyo (Sean Institute, 2023)
One indicator of the quality of health services is the Maternal Mortality Rate (MMR). Causes of death are complications during pregnancy, childbirth and the puerperium, but most can be prevented if accompanied by good coverage and quality of services. The referral system is one way to deal with complications and delays in maternal health services. The purpose of this research is to get an overview of the maternal referral system in Indonesia. This study uses the literature review method with a qualitative fishbone diagram analysis approach that analyzes the components of man, method, machine, and material. The articles in this study were obtained through the PubMed, Scopus, Science Direct and Google Scholar databases with the year of publication 2015-2023. Obstacles in the implementation of the maternal referral system reported from the seven referral articles were limited trained staff, lack of staff understanding of SOP, communication between health workers, information systems between referring health facilities and referral receiving health facilities that were not optimal, lack of support for facilities and infrastructure, as well as from the family and mother side in the form of approval and late decision making. To improve the quality of the maternal referral system, it is necessary to thoroughly evaluate the effectiveness of the referral system, conduct training and education of health workers regarding emergencies and SOPs for maternal referrals, increase the availability of medical devices and medicines by increasing the distribution of drugs to areas where they are needed, develop an information system and an integrated administration system for maternal referrals.